Chloroquine and Hydroxychloroquine for the Prevention and Treatment of COVID-19: A Fiction, Hope or Hype? An Updated Review - Saghir SAM; AlGabri NA; Alagawany MM; Attia YA; Alyileili SR; Elnesr SS; Shafi ME; Al-shargi OYA; Al-balagi N; Alwajeeh AS; Alsalahi OS; Patra AK; et al. (Dove Medical Press, 2021)
Sultan AM Saghir,1 Naif A AlGabri,2,3 Mahmoud M Alagawany,4 Youssef A Attia,5,6 Salem R Alyileili,7 Shaaban S Elnesr,8 Manal E Shafi,9 Omar YA Al-shargi,10 Nader Al-balagi,11 Abdullah S Alwajeeh,12 Omar SA Alsalahi,13 Amlan K Patra,14 Asmaa F Khafaga,15 Ahmed Negida,16,17 Ahmed Noreldin,18 Wesam Al-Amarat,19 Amer A Almaiman,20 Khaled A El-Tarabily,21,22 Mohamed E Abd El-Hack4 1Department of Medical Analysis, Princess Aisha Bint Al-Hussein College of Nursing and Medical Sciences, Al-Hussein Bin Talal University, Ma’an, 71111, Jordan; 2Pathology Department, Faculty of Veterinary Medicine, Thamar University, Dhamar, Yemen; 3Laboratory of Regional Djibouti Livestock Quarantine, Abu Yasar International Est. 1999, Djibouti, Djibouti; 4Department of Poultry, Faculty of Agriculture, Zagazig University, Zagazig, 44511, Egypt; 5Department of Agriculture, Faculty of Environmental Sciences, King Abdulaziz University, Jeddah, 21589, Kingdom of Saudi Arabia; 6Department of Animal and Poultry Production, Faculty of Agriculture, Damanhour University, Damanhour, Egypt; 7Department of Integrative Agriculture, College of Food and Agriculture, United Arab Emirates University, Al-Ain, 15551, United Arab Emirates; 8Department of Poultry Production, Faculty of Agriculture, Fayoum University, Fayoum, 63514, Egypt; 9Department of Biological Sciences, Zoology, King Abdulaziz University, Jeddah, 21589, Kingdom of Saudi Arabia; 10Department of Pharmacology, College of Pharmacy, Riyadh Elm University, Riyadh, Kingdom of Saudi Arabia; 11Ministry of Health, Riyadh, Kingdom of Saudi Arabia; 12Anti-DopingLab, Doha, Qatar; 13Department of Medical Laboratories, Faculty of Medicine and Health Sciences, Hodeidah University, Al Hodaidah, Yemen; 14Department of Animal Nutrition, West Bengal University of Animal and Fishery Sciences, Belgachia, Kolkata, India; 15Department of Pathology, Faculty of Veterinary Medicine, Alexandria University, Edfina, 22758, Egypt; 16School of Pharmacy and Biomedical Sciences, University of Portsmouth, Portsmouth, UK; 17Zagazig University Hospitals, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 18Histology and Cytology Department, Faculty of Veterinary Medicine, Damanhour University, Damanhour, 22511, Egypt; 19Department of Medical Support, Al-Karak University College, Al-Balqa’ Applied University, Salt, Jordan; 20Department of Applied Medical Sciences, Community College of Uniazah, Qassim University, Buraydah, 51431, Kingdom of Saudi Arabia; 21Department of Biology, College of Science, United Arab Emirates University, Al-Ain, 15551, United Arab Emirates; 22Biosecurity and One Health Research Centre, Harry Butler Institute, Murdoch University, Murdoch, Western Australia, 6150, AustraliaCorrespondence: Youssef A Attia; Khaled A El-Tarabily Email yaattia@kau.edu.sa; ktarabily@uaeu.ac.aeAbstract: In December 2019, the novel coronavirus disease pandemic (COVID-19) that began in China had infected so far more than 109,217,366 million individuals worldwide and accounted for more than 2,413,912 fatalities. With the dawn of this novel coronavirus (SARS-CoV-2), there was a requirement to select potential therapies that might effectively kill the virus, accelerate the recovery, or decrease the case fatality rate. Besides the currently available antiviral medications for human immunodeficiency virus (HIV) and hepatitis C virus (HCV), the chloroquine/hydroxychloroquine (CQ/HCQ) regimen with or without azithromycin has been repurposed in China and was recommended by the National Health Commission, China in mid-February 2020. By this time, the selection of this regimen was based on its efficacy against the previous SARS-CoV-1 virus and its potential to inhibit viral replication of the SARS-CoV-2 in vitro. There was a shortage of robust clinical proof about the effectiveness of this regimen against the novel SARS-CoV-2. Therefore, extensive research effort has been made by several researchers worldwide to investigate whether this regimen is safe and effective for the management of COVID-19. In this review, we provided a comprehensive overview of the CQ/HCQ regimen, summarizing data from in vitro studies and clinical trials for the protection against or the treatment of SARS-CoV-2. Despite the initial promising results from the in vitro studies and the widespread use of CQ/HCQ in clinical settings during the 1st wave of COVID-19, current data from well-designed randomized controlled trials showed no evidence of benefit from CQ/HCQ supplementation for the treatment or prophylaxis against SARS-CoV-2 infection. Particularly, the two largest randomized controlled trials to date (RECOVERY and WHO SOLIDARITY trials), both confirmed that CQ/HCQ regimen does not provide any clinical benefit for COVID-19 patients. Therefore, we do not recommend the use of this regimen in COVID-19 patients outside the context of clinical trials.Keywords: antiviral drugs, chloroquine, COVID-19, drug safety, hydroxychloroquine, SARS-CoV-2, treatments